Essentials of Pharamacology - Shah Nawaz (Karachi Paramount Books Pvt Ltd, 2023)
"Lippincott Illustrated Reviews: Pharmacology, Seventh Edition, is the updated, enhanced version of the student-favorite resource for essentials of medical pharmacology. The first-and-best resource, the Lippincott Illustrated Reviews series features clear, effective writing and hundreds of illustrations for ideal rapid review and the assimilation of complex information. Clear, sequential images present mechanisms of action and focus on showing rather than telling students how drugs work. Nearly 600 annotated, full-color illustrations visually explain complex processes! Outline format ideal for concise review and foundational learning.
Include Index
Keywords: Pharmacology -- Examinations